Effect of co-treatment with doxorubicin and verapamil loaded into chitosan nanoparticles on diethylnitrosamine-induced hepatocellular carcinoma in mice. (November 2020) - Abo Mansour, HE; El-Batsh, MM; Badawy, NS; Mehanna, ET; Mesbah, NM; Abo-Elmatty, DM
This study aimed to investigate the potential role of co-treatment with doxorubicin (DOX) and verapamil (VRP) nanoparticles in experimentally induced hepatocellular carcinoma in mice and to investigate the possible mechanisms behind the potential favorable effect of the co-treatment. DOX and VRP were loaded into chitosan nanoparticles (CHNPs), and cytotoxicity of loaded and unloaded drugs against HepG2 cells was evaluated. Male albino mice were divided into eight groups ( n = 15): (1) normal control, (2) diethylnitrosamine, (3) CHNPs, (4) free DOX, (5) CHNPs DOX, (6) free VRP, (7) CHNPs VRP, and (8) CHNPs DOX + CHNPs VRP. Either VRP or DOX loaded into CHNPs showed stronger growth inhibition of HepG2 cells than their free forms. DOX or VRP nanoparticles displayed pronounced anticancer activity in vivo through the decline of vascular endothelial growth factor and B cell lymphoma-2 contents in liver tissues, upregulation of antioxidant enzymes, and downregulation of multidrug resistance 1. Moreover, reduced cardiotoxicity was evident from decreased level of tumor necrosis factor-α and malondialdehyde in heart tissues coupled with decreased serum activity of creatine kinase-myocardial band and lactate dehydrogenase. Co-treatment with CHNPs DOX and CHNPs VRP showed superior results versus other treatments. Liver sections from the co-treatment group revealed the absence of necrosis, enhanced apoptosis, and nearly normal hepatic lobule architecture. Co-treatment with CHNPs DOX and CHNPs VRP revealed enhanced anticancer activity and decreased cardiotoxicity versus the corresponding free forms.